INDIVIDUAL APPROACH TO LEARNING AS A COMPONENT OF SUCCESS STUDY IN HIGHER EDUCATIONAL INSTITUTIONS - Savchenko, L.O. (Pedagogy of Higher and Secondary Education, 2010)
In article, the problem of introduction of an individual approach in process of creating of students in higher educational institutions is considered.